(untitled) (Praxis Educativa, 2022)
The article problematizes the enactment of the National Plan for the Completion of Primary and Secondary Studies in the province of La Pampa, Argentina. From a socio-political perspective, we analyze the jurisdictional strategy promoted by ministerial actors to sustain, within the framework of the national underfunding of politics, their schooling proposal. We propose that the precariousness that marks the FinEs Plan and its financing also produces the precarious, but more efficient conditions to make the right to education an act of provincial will that enables us to sustain the meaning of the Plan, but without the allocation of resources.